En Bloc Tumor Resection, Optical Molecular Imaging, and the Potential Synergy of the Combination of the Two Techniques in Bladder Cancer - Yang, Yongjun; Liu, Chao; Yan, Xiaoting; Li, Jiawei; Yang, Xiaofeng (Frontiers in Oncology, 2021)
Although transurethral resection of bladder tumor is the golden standard for the treatment of non-muscle invasive bladder cancer, this surgical procedure still has some serious drawbacks. For example, piecemeal resection of tumor tissue results in exfoliated tumor cells dissemination and implantation, and fragmented tumor specimens make it difficult for pathologists to accurately assess the pathological stage and histologic grade. En bloc tumor resection follows the basic principle of oncological surgery and provides an intact tumor specimen containing detrusor muscle for pathologists to make accurate histopathological assessment. However, there is no robust clinical evidence that en bloc tumor resection is superior to conventional resection in terms of oncological outcomes. Considering the high recurrence rate, small or occult tumor lesions may be overlooked and incomplete tumor resection may occur during white light cystoscopy-assisted transurethral resection. Molecular fluorescent tracers have the ability to bind tumor cells with high sensitivity and specificity. Optical molecular imaging mediated by it can detect small or occult malignant lesions while minimizing the occurrence of false-positive results. Meanwhile, optical molecular imaging can provide dynamic and real-time image guidance in the surgical procedure, which helps urologists to accurately determine the boundary and depth of tumor invasion, so as to perform complete and high-quality transurethral tumor resection. Integrating the advantages of these two technologies, optical molecular imaging-assisted en bloc tumor resection shows the potential to improve the positive detection rate of small or occult tumor lesions and the quality of transurethral resection, resulting in high recurrence-free and progression-free survival rates.